2021
DOI: 10.1111/bpa.12958
|View full text |Cite
|
Sign up to set email alerts
|

Application of single cell genomics to focal epilepsies: A call to action

Abstract: Focal epilepsies are the largest epilepsy subtype and associated with significant morbidity. Somatic variation is a newly recognized genetic mechanism underlying a subset of focal epilepsies, but little is known about the processes through which somatic mosaicism causes seizures, the cell types carrying the pathogenic variants, or their developmental origin. Meanwhile, the inception of single cell biology has completely revolutionized the study of neurological diseases and has the potential to answer some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 191 publications
(235 reference statements)
1
8
0
Order By: Relevance
“…Analysis of pools of microdissected cells demonstrated that dysmorphic neurons and balloon cells carry the pathogenic variants leading to hyperactivation of mTOR 19,51,64 . These discoveries offer the opportunity to reshape the genetic landscape of FCD, distinguishing mTOR and non–mTOR‐related FCD toward a new integrated genotype–phenotype classification 12,13,66 . The current challenge is whether genetic findings can predict surgery outcome, the extent of the lesion, and the presence of multiple or bilateral lesions 67 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of pools of microdissected cells demonstrated that dysmorphic neurons and balloon cells carry the pathogenic variants leading to hyperactivation of mTOR 19,51,64 . These discoveries offer the opportunity to reshape the genetic landscape of FCD, distinguishing mTOR and non–mTOR‐related FCD toward a new integrated genotype–phenotype classification 12,13,66 . The current challenge is whether genetic findings can predict surgery outcome, the extent of the lesion, and the presence of multiple or bilateral lesions 67 .…”
Section: Resultsmentioning
confidence: 99%
“…19,51,64 These discoveries offer the opportunity to reshape the genetic landscape of FCD, distinguishing mTOR and non-mTOR-related FCD toward a new integrated genotypephenotype classification. 12,13,66 The current challenge is whether genetic findings can predict surgery outcome, the extent of the lesion, and the presence of multiple or bilateral lesions. 67 Overall mTOR-related MCD with germline or germline and somatic variants have a better surgical outcome than MCD caused by mutations in ion channel and synaptic transmission genes.…”
Section: Mild Malformations Of Cortical Development With Oligodendrog...mentioning
confidence: 99%
“…Taken together, it is highly likely that somatic mutation AKT1 E17K might occur during the stage of progenitor cells of the bilateral dorsal forebrain with unique spatio-temporal gradients. 6,15 The PIK3CA, AKT1, and MTOR genes encode wellknown regulators of the mTOR signaling pathway, which is involved in cell growth and metabolism, [4][5][6] and its activation is observed in apical progenitor cells and the cortical plate in developing murine cerebral cortex, suggesting that this signaling is involved in multiple steps of cerebral development, including cell proliferation, differentiation of stem/progenitor cells, and migration in cortical development. 2 In cases 1 and 2, we observed that cell nests immunoreactive for P-RPS6 (Ser240/244) were scattered in the polymicrogyria-like cortical plate, intermediate zone, and arachnoid space, suggesting that the PI3K-AKT-MTOR pathway was actually activated in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its experimental operation is more tedious and lacks repeatability. 77 Therefore, the future development of LIANTI needs to be further explored.…”
Section: Isothermal Amplification Technologymentioning
confidence: 99%
“…It is highly dependent on Tn5 transposase and has not yet achieved large‐scale application. Moreover, its experimental operation is more tedious and lacks repeatability 77 . Therefore, the future development of LIANTI needs to be further explored.…”
Section: Isothermal Amplification Technologymentioning
confidence: 99%